The Effect of the Methyl Functional Group on the Physicochemical and Structural Properties of a Synthesized Semi-Aromatic Polyimides - R. Ahmadi; H. Sanaeepur; A. Ebadi Amooghin (Iranian Journal of Chemical Engineering)
It is crucial to design and develop new polymers with desirable characteristics. Aromatic polyimides have been attracted more attention in comparison with other polymeric materials, because of their excellent properties, such as the high thermal stability, mechanical strength, and chemical resistance. In this work, two semi-aromatic polyimides (BCDA-mPDA and BCDA-Durene) were successfully synthesized from bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarbocylic dianhydride (BCDA), 1,3-phenylenediamine (mPDA), and 2,3,5,6-tetramethyl-1,4-phenylenediamine (Durene) to investigate the effect of methyl functional groups on the physicochemical and structural properties of the synthesized polyimides. The synthesized polyimides were characterized by the proton nuclear magnetic resonance (1H-NMR) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) spectroscopy, inherent viscosity measurement, and solubility test. FTIR and 1H-NMR results confirmed the chemical structure of the synthesized polyimides. XRD results showed that the presence of bulky methyl groups has led to increasing amorphous regions in the polymer structure. In addition, these new polymers were soluble in various organic solvents such as dimethylformamide (DMF), dimethylsulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP). The inherent viscosity of the synthesized polyimides was 0.65 dl/g for BCDA-Durene and 0.96 dl/g for BCDA-mPDA, which indicates the moderate molecular weight of the polymers.